The Role of Teachers in Instilling Disciplined Character Through PPKn Learning for Grade V Students at YPK Ishak Semuel Kijne Wadio Elementary School, Nabire - Selpi Dogomo; Nona Anisa Aprilia; Abihut Nerius Pakage; Nolince Pakage; Irsa Tandi Lolok; Santji Afi Rangkoly (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2026)
Research This aim for know the role of teachers in implant character discipline in students through the learning process in class V. Research held at YPK Ishak Semuel Kijne Wadio Elementary School, Nabire with use method descriptive and approach qualitative. Subject study consists of above the fifth grade teacher and 3 students class V. Data collection techniques were carried out through observation, interviews, and documentation. The data obtained analyzed use technique data reduction, data presentation, and data extraction conclusion. Research results show that teachers have role important in form character discipline student through exemplary behavior, habituation, giving motivation, as well as implementation rule during the learning process taking place. Teachers also active give direction and reinforcement to students to get used to it behave discipline in activity Study and life everyday. Although there is a number of obstacle like lack of awareness students and influence environment family, efforts made by teachers in a way consistent capable help increase attitude discipline students. With Thus, learning at school base become effective means in support formation character discipline student since age early.